An integrated approach using morphological, biochemical, and RAPD markers to assess the genetic diversity of Olive (Olea Europaea L.) cultivars in India - Smita Sisodiya; Mousumi Debnath; Devendra Jain; Surinder Singh Shekhawat (Scientific Reports)
Abstract Olive cultivation in Rajasthan, India, has recently gained significant attention. To understand the genetic diversity among the cultivars of olive (Olea europaea L.) grown in Rajasthan, India, a cumulative approach using Random Amplified Polymorphic DNA (RAPD) markers was employed. This approach was based on morphological, biochemical, nutritional, and associated markers like antimicrobial and antioxidant potential linked to the functional activity of the primary and secondary metabolites. Eight primers (OPA-1, OPA2, OPA3, OPA4; OPB1, OPB2, OPB3, and OPB4) were used to differentiate the seven cultivars of olive. The results indicated 51 reproducible bands showing 45 polymorphism bands (88.23%). The disparity among the cultivars was evident, encompassing their morphological characteristics, biochemical features (protein, fat, carbohydrate, total phenolics, flavonoid, DPPH IC50, radical scavenging activity), and their inhibitory responses against different microorganisms. The genetic analysis using an unweighted pair group method with arithmetic averaging revealed diversity, and the dendrogram formed four distinct groups. These results demonstrate the molecular variance allowing the genetic diversity between the seven exotic cultivars imported from Israel. Considering the aforementioned phylogenetic study, this innovative method can potentially aid in understanding the future crop breeding initiatives in India and the improvement of olives.